2002
DOI: 10.2172/799627
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring microbe-induced physical property changes using high-frequency acoustic waveform data: Toward the development of a microbial megascope

Abstract: A laboratory investigation was undertaken to determine the effect of microbe generated gas bubbles in controlled, saturated sediment columns utilizing a novel technique involving acoustic wave propagation.Specifically, the effect of denitrifying bacteria on saturated flow conditions was evaluated in light of the stimulated production of N 2 gas and the resulting plugging of the pore throats. The propagation of high frequency acoustic waves through the sediment columns was used to locate those regions in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…[6] Most biogeophysical investigations have focused on geoelectrical techniques (see, for example, reviews by Atekwana et al [2006] and Atekwana and Slater [2009]) for the investigation of temporal microbial-induced phenomena. Recent studies have focused on the effect of biogenic gases or microbial mediated mineral precipitation on wave propagation in sands and sediments [e.g., Williams, 2002;Williams et al, 2005;DeJong et al, 2006DeJong et al, , 2010. The present study advances the work of Williams et al [2005] and DeJong et al…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…[6] Most biogeophysical investigations have focused on geoelectrical techniques (see, for example, reviews by Atekwana et al [2006] and Atekwana and Slater [2009]) for the investigation of temporal microbial-induced phenomena. Recent studies have focused on the effect of biogenic gases or microbial mediated mineral precipitation on wave propagation in sands and sediments [e.g., Williams, 2002;Williams et al, 2005;DeJong et al, 2006DeJong et al, , 2010. The present study advances the work of Williams et al [2005] and DeJong et al…”
Section: Introductionsupporting
confidence: 53%
“…Previous seismic studies have demonstrated that seismic methods are sensitive to the products of microbial activity in porous media, such as the production of biogenic gas [ Williams , 2002] and enhanced biomineralization [ Williams et al , 2005; DeJong et al , 2006]. Based on the fact that mineral precipitation was not induced or enhanced in our current experiment, and no large gas bubble formation was observed on the sides of the biostimulated columns (unlike that of Williams [2002]), we attribute the observed amplitude variation in the biostimulated sample in these experiments to biofilm development. This attribution is based on the observed microbes and biofilms in the ESEM images of samples at locations with enhanced/reduced acoustic attenuation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This bacterium was successfully used to produce extensive gas bubbles in a column study (Williams, 2002). Microbiological aspects of the Williams study were conducted under the mentoring of PNNL microbiologist Fred Brockman.…”
Section: Appendixmentioning
confidence: 99%
“…Recent work has investigated the sensitivity of various geophysical measurements to the injection of amendments and to the associated system transformations. These studies have included the use of Induced Polarization and acoustic methods to track changes in iron mineralogy during sulfate reduction at the laboratory scale (Williams et al 2005a(Williams et al , 2005bNtarlagiannis et al 2005), the use of radar and acoustic methods to detect the onset and evolution of gas at the laboratory and field scales (Williams et al 2003), the use of radar and electrical methods for monitoring changes in pore fluid ionic strength at the laboratory and field scales , and the use of Spontaneous Potential (SP) measurements for characterization of redox conditions at the field scale (Williams et al 2005c).…”
Section: Appendix C C1 Backgroundmentioning
confidence: 99%